Innovation in the subsistence marketplace: an analysis considering multiple concepts and approaches - Vitor Koki da Costa Nogami; Andres Rodriguez Veloso (Innovation & Management Review, 2021)
Purpose The purpose of this paper is to explore the different concepts of innovation in the subsistence marketplace from top-down and bottom-up approaches. This study analyzes the literature on the theme and identified research gaps by constructing a framework based on approaches and innovation concepts, which can guide future research efforts. Additionally, this paper presents two case studies, which can improve the way innovation is developed and diffused in the subsistence marketplace. Design/methodology/approach Through a literature review, this study develops a framework by analyzing innovation concepts in the subsistence marketplace (i.e. base of the pyramid innovation, disruptive innovation, frugal innovation, reverse innovation and inclusive innovation) in light of subsistence marketplace approaches (top-down and bottom-up). Findings The analysis showed critical research gaps, especially a lack of studies involving disruptive and frugal innovations from a bottom-up approach. This paper also concludes that the top-down approach is more common than the bottom-up one. To fill these gaps, this study presents two business plans by illustrating disruptive innovation vs bottom-up approach and frugal innovation vs bottom-up approach. Originality/value The use of real business plans to illustrate proposals having an actual impact on subsistence marketplace regions sheds light on how to address these challenges. By doing so, this paper intends to fill the theoretical gap in disruptive and frugal innovations within a bottom-up approach to promote the development and diffusion of different types of innovation in the subsistence marketplace, and thus provide solutions to alleviate poverty.
Keywords: 650; BoP innovation; Disruptive innovation; Frugal innovation; Reverse innovation; Subsistence marketplace; Top-down and bottom-up